APEXIFICATION FOLLOWED BY DIRECT COMPOSITE VENEER ON ELLIS CLASS IV FRACTURE: A CASE REPORT - Effendi Halim; Yoanita Dwiaidina; Wignyo Hadriyanto; Pribadi Santosa; Ema Mulyawati; Yulita Kristanti (Odonto : Dental Journal, 2022)
Introduction: Traumatized immature permanent teeth can cause pulp necrosis, leading to imperfect root formation, and thus resulting an open apex. The apical opening of the immature teeth is mostly large and thus may lead to difficulties in performing a root filling. In such cases, apexification is mandatory before doing root canal treatment. The aim of this case report was to inform that apexification and direct veneer was suitable to treat Ellis class IV fracture with necrotic pulpCase Report: 21-year-old female came to the Dental Conservation Clinic RSGM Prof. Soedomo Faculty of Dentistry UGM with chief complaint of right central incisive maxilla fracture and tooth discoloration. Radiographic examination showed an open apex of tooth 11 with a diffuse apical radiolucent area. Root canal treatment and apexification were carried out using circumferential technique and Mineral Trioxide Aggregate (MTA). Vertical warm obturation was performed, followed by intra coronal bleaching in the next visit. Final restoration was carried out using direct composite veneer. Post treatment radiographic showed a 1 mm diameter of radiolucent area at the apex in a good healing process.Conclusion: Apexification using MTA can be used to treat an open apex tooth. 1Student of Specialist Programme in Conservative Dentistry, Dentistry Faculty, Gadjah Mada University 2Department of Conservative Dentistry, Dentistry Faculty, Gadjah Mada University